(untitled) (Revista de Ciências Agroveterinárias, 2020)
The objective of the research was to evaluate the residual effect of the seeds treatment with fungicide and silicate fertilizer in the control of brown spot in the vegetative stage of the barley plant. The experiment was a two-way factorial with four seed treatments (ST): control (distilled water), fungicide (triadimenol), silicate fertilizer and the fungicide + silicate fertilizer and three periods of 30, 45 and 60 days after emergence (DAE). Barley plants were inoculated with a spore suspension of Bipolaris sorokiniana. The disease severity assessment over time was used to calculate the area under the brown spot progress curve (AUCPBS). At 30 DAE, fungicide treatment was the most efficient with reduction of 64% in the AUCPBS, followed by silicate fertilizer with 56%. The mixture also reduced AUCPBS, but with lower efficiency than isolated products.